2020
DOI: 10.1002/ehf2.12897
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of a risk‐guided strategy for reducing readmissions for acute decompensated heart failure: the Risk‐HF study

Abstract: Aims Heart failure (HF) readmission commonly arises owing to insufficient patient knowledge and failure of recognition of the early stages of recurrent fluid congestion. In previous work, we developed a score to predict short-term hospital readmission and showed that higher-risk patients benefit most from a disease management programme (DMP) that included enhancing knowledge and education by a nurse. We aim to evaluate the effectiveness of a novel, nurse-led HF DMP in selected patients at high risk of short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(81 reference statements)
0
5
0
2
Order By: Relevance
“…Of these studies, eight were completed and reported clinical outcomes ( 15 17 , 27 , 29 , 30 , 32 , 33 ). However, the other two studies were still in the process of subject enrollment ( 28 , 31 ). A total of three RCTs ( 27 , 30 , 31 ) enrolled patients with AHF, five RCTs ( 15 , 16 , 28 , 29 ) enrolled patients with CHF, and one RCT ( 30 ) enrolled patients with CHF plus pulmonary artery hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these studies, eight were completed and reported clinical outcomes ( 15 17 , 27 , 29 , 30 , 32 , 33 ). However, the other two studies were still in the process of subject enrollment ( 28 , 31 ). A total of three RCTs ( 27 , 30 , 31 ) enrolled patients with AHF, five RCTs ( 15 , 16 , 28 , 29 ) enrolled patients with CHF, and one RCT ( 30 ) enrolled patients with CHF plus pulmonary artery hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…However, the other two studies were still in the process of subject enrollment ( 28 , 31 ). A total of three RCTs ( 27 , 30 , 31 ) enrolled patients with AHF, five RCTs ( 15 , 16 , 28 , 29 ) enrolled patients with CHF, and one RCT ( 30 ) enrolled patients with CHF plus pulmonary artery hypertension. Another RCT ( 33 ) enrolled subjects admitted to hospital with cardiopulmonary symptoms, nearly half of whom were diagnosed with AHF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations